URGENCY OF THE FIFTH AMENDMENT OF THE INDONESIAN 1945 CONSTITUTION - Suparman Marzuki; Despan Heryansyah; Sahid Hadi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This article focuses on the idea of a fifth amendment to the Indonesian constitution, namely an amendment to the UUD NRI 1945. Stressing today’s constitutional problems, which we identify as deriving from the norms in the UUD NRI 1945, this article presents the urgency of the fifth amendment and how to bring about a democratic constitution. Using a statutory and conceptual approach, this normative study identifies a number of foundational issues in the UUD NRI 1945. Thus, the fifth amendment of the constitution finds its urgency. Through this article, we encourage the fifth amendment to be conducted to present a democratic constitution, both materially and formally.